Activation of TRPC6 by AngⅡ Induces Podocyte Injury and Participates in Proteinuria of Nephrotic Syndrome - Feng, Ye; Li, Manman; Wang, Yunlai; Yang, Mo; Shi, Gaoxiang; Yin, Dengke; Xuan, Zihua; Xu, Fan (Frontiers in Pharmacology, 2022)
Background: Nephrotic syndrome (NS) is a common glomerular disease, and podocyte injury is the character of primary NS, usually caused by minimal change disease and membranous nephropathy. Podocytopathy is primarily associated with glomerular proteinuria. Losartan, an angiotensin receptor blocker (ARB), is commonly used in the treatment of NS, and the AngiotensinⅡ (AngⅡ)–transient receptor potential ion channel 6 (TRPC6) axis has been reported to act on podocytes to regulate proteinuria in NS. Therefore, the purpose of this study was to explore the relationship in between AngⅡ–TRPC6, podocyte injury, and proteinuria based on the adriamycin (ADR) NS rat model. Method: All male rats were divided into three groups: control group, model group, and ARB group. The rats in the model group were induced by ADR, and the rats in the ARB group received losartan after induction of renal injury for 4 weeks. The changes in parameters related to renal dysfunction, and glomerular and podocyte structural damage, such as AngⅡ, AngⅡ type I receptor (AT1R), TRPC6, CaN, Caspase-3, Nephrin, and Podocin, were analyzed. Furthermore, the kidneys were isolated for study via transmission electron microscopy (TEM), immunohistochemistry, and western blot (WB) after the rats were sacrificed. In vitro, immortalized mouse MPC5 podocytes were used to investigate the regulatory effect of flufenamic acid (Flu) and SAR7334 (SAR) on the AngⅡ-TRPC6 signaling axis. Flow cytometry and WB were conducted to determine the relationship between podocyte injury and AngⅡ-TRPC6. Results:In vivo results showed that NS rats developed massive albuminuria and abnormal renal function, accompanied by abnormally increased levels of AngⅡ, TRPC6, AT1R, and CaN and a decreased expression of actin molecules in podocytes, extensive fusion of foot processes (FP), loss of glomerular structural integrity, collapse of podocyte structure, and skeletal reorganization. In vitro experiments indicated that both AngⅡ and Flu (the specific agonist of TRPC6) stimulated the expressions of TRPC6, AT1R, and Caspase-3 in podocytes. The AngⅡ receptor–blocker losartan and TRPC6-specific inhibitor SAR blocked the overexpression of the aforementioned proteins. In addition, SAR also attenuated the degradation of podocyte structural proteins and inhibited the fluorescence intensity of intracellular calcium (Ca2+) and cell apoptosis. Conclusion: The involvement of AngⅡ in the occurrence of NS proteinuria may be related to podocyte injury induced by activated TRPC6.